PICMET '09 - 2009 Portland International Conference on Management of Engineering &Amp; Technology 2009
DOI: 10.1109/picmet.2009.5261946
|View full text |Cite
|
Sign up to set email alerts
|

E-business adoption in Iranian small and medium enterprises: Analyzing and prioritizing the extra-organizational factors

Abstract: The main purpose of this research is to investigate and prioritize the extra-organizational E-business adoption factors among Iranian small and medium enterprises (SMEs). The research is structured around the two dimensions of extraorganizational or exogenous factors. These dimensions are environmental factors (a set of economical, political, social,legal and market/industry issues) and technological factors (Ebusiness technologies characteristics). After conducting an indeep literature review and eliciting th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…However, there are, and would definitely be, barriers associated with SMEs implementing ICTs at a wider level in order to increase national competitiveness. Further literature can be found on the existing barriers to adoption of ICTs by Iranian SMEs (see Houraliet al, 2008;Sameni & Khoshalhan, 2009;Hajliet al, 2014;Yasin et al, 2014). For instance, ICT solutions and the technological sophistication brought by it should be cost-effective in order to make it possible for firms to implement it.…”
Section: Related and Supporting Industriesmentioning
confidence: 99%
“…However, there are, and would definitely be, barriers associated with SMEs implementing ICTs at a wider level in order to increase national competitiveness. Further literature can be found on the existing barriers to adoption of ICTs by Iranian SMEs (see Houraliet al, 2008;Sameni & Khoshalhan, 2009;Hajliet al, 2014;Yasin et al, 2014). For instance, ICT solutions and the technological sophistication brought by it should be cost-effective in order to make it possible for firms to implement it.…”
Section: Related and Supporting Industriesmentioning
confidence: 99%
“…11, No. 10; Despite the noticeable efforts clarifying EC adoption phenomenon in Iranian SMEs (i.e., Ghamatrasa, 2006;Ajdari, 2007;Afzal, 2008;Hajkarimi & Azizi, 2008;Sanayei & Rajabion, 2009 ;Ghorishi, 2009;Sameni & Khoshalhan, 2009;Abbasi, Sarlak, Ghorbani, & Esfehani, 2010;Ghobakhloo, Aranda, & Amando, 2011a;Ghobakhloo, Aranda, & Amando, 2011b;Hajli & Bugshan, 2012); there is almost no related study in family SMEs' context in Iran. Furthermore, the significant differences in terms of EC adoption, between large-sized and SMEs, Non-family SMEs and family SMEs, and also developing and developed countries had made the usage of existing SMEs' EC adoption models and findings not quite appropriate to explain EC adoption in family SMEs.…”
Section: Literature Review and Propositions Developmentmentioning
confidence: 99%
“…Zhu et al, 2003). In case of Iranian SMEs, Ghobakhloo et al (2011b), Afzal (2008), Sameni andKhoshalhan (2009), Sanayei andRajabion (2009) have done some related studies. These studies indicated that the lack of national readiness, in terms of technological, social, cultural, legal, logistical, and financial structures, was the major inhibitor stalling the uptake of EC in developing countries.…”
Section: Perceived National (Ec) Structurementioning
confidence: 99%
See 1 more Smart Citation
“…SMEs engaged in the apparel retail market suffer from inadequate organizational planning and sales strategies (Tetteh & Burn, 2001). In contrast to large firms, SMEs are different in terms of the scope of the products or service varieties available to the customers (Reynolds, Savage, & Williams, 1994;Sameni & Khoshalhan, 2009), as well as sales strategies, leading to the next research question:…”
Section: Drivers Of Apparel Consumption In the Vietnamese Retail Marketmentioning
confidence: 99%